The Effect of Duck Manure Fermentation Subtitution for Juvenile Catfish Feed (Clarias sp.) - Baruna Kusuma; Esna Dili Novianto (Journal of Aquaculture Development and Environment, 2018)
Pellet is replaceable with fermented duck manure in the catfish. The effect of substitution pellet feed juvenile catfish with fermented duck manure was investigated. It can be done by fermentation process of duck manure by yeast from traditional food starter called Tape. It contains yeast of genus Aspergilius, Saccharomyces, Candida, Hansenulla, dan Acetobacter bacteria. Catfish diets supplemented with 5% pellet/fish/day (W/W/day). Four treatments diets were 45% (A), 30% (B), 15% (C) and 0% (D) levels of duck manure from total weight and it fed to catfish juvenile (weight 2,75±0,05 g) for 30 days controlled aquaria. The results of this studies found that the recommended diet was diet C and D formulations beacuse it can provide catfish juvenile growth response. Duck manure can replace feed juvenile catfish by fermentation for maximmum 15% from catfish diets.